Multi-Criteria Decision Analysis of Entrepreneurial Orientation and Business Performance in Nigeria - Adebiyi Sulaimon Olanrewaju (Economics and Business, 2019)
This study advances research on entrepreneurial orientation and business performance by assessing, prioritizing, ranking, and evaluating decision choices among entrepreneurial orientation attributes that influence small and medium scale enterprise performance in Nigeria. Data were gathered through the multi-criteria decision-making (MCDM) tool called analytic hierarchy process (AHP) based questionnaire administered to practicing entrepreneurs in Lagos State, Nigeria. The population of the study consists of all the firms (mainly small and medium scale businesses) registered by Lagos Chamber of Commerce, totalling 1766 at the time of this study. The sample size was calculated through Yamane formula, while entrepreneurs managing the sampled firms were the respondents carefully selected for the study through a random sampling procedure. Data collected were analysed through descriptive statistics and analytic hierarchy process procedures for eliciting the consistency ratio, consistency index, Lambda Max, local and global priority values for an effective policy decision. The priorities were established in line with the AHP framework using pairwise comparisons and judgment of entrepreneurs. The results revealed the preference of entrepreneurial orientation dimension that influenced business performance most based on pairwise experiences and trade-off of different attributes. This study explores the application of AHP methodology for measuring complex entrepreneurial decision-making process for enhancing business performance. Thus, the AHP revealed a potential research method in computing weights and chasing MCDM process.